2012
DOI: 10.1002/stem.1101
|View full text |Cite
|
Sign up to set email alerts
|

Xenotransplanted Embryonic Kidney Provides a Niche for Endogenous Mesenchymal Stem Cell Differentiation into Erythropoietin-Producing Tissue

Abstract: Recent findings have demonstrated that stem cells can differentiate into mature tissue when supplied with a niche containing factors identical to those in the normal developmental program. A niche for the development of an organ can be provided by xenotransplantation of a similar developing organ. However, this process has many technical, safety, and ethical concerns. Here, we established xenotransplantation models that control endogenous mesenchymal stem cell (MSC) differentiation into mature erythropoietin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
(37 reference statements)
2
36
0
Order By: Relevance
“…This idea is supported by the observation that kidney progenitor cells produce renal tubules and glomeruli but not blood vessels or interstitial tissues, which contain REP cells (Matsumoto et al 2012;Taguchi et al 2014).…”
Section: Renal Epo-producing (Rep) Cellsmentioning
confidence: 90%
“…This idea is supported by the observation that kidney progenitor cells produce renal tubules and glomeruli but not blood vessels or interstitial tissues, which contain REP cells (Matsumoto et al 2012;Taguchi et al 2014).…”
Section: Renal Epo-producing (Rep) Cellsmentioning
confidence: 90%
“…Pig metanephroi were cryopreserved using the previously reported vitrification method (8,20), with slight modifications. Briefly, metanephroi were initially equilibrated with 7.5% (vol/vol) ethylene glycol (EG) and 7.5% (vol/vol) DMSO in handling medium [HM; 20 mM Hepes-buffered tissue culture medium 199 + 20% (vol/vol) calf serum] for 25 min, followed by a second equilibration in vitrification solution (VS), consisting of 15% (vol/vol) EG and 15% (vol/vol) DMSO in HM, for 20-50 min, on ice.…”
mentioning
confidence: 99%
“…Matsumoto et al [6] recently showed that xenotransplanted metanephros could supply endogenous mesenchymal stem cells with a niche for differentiation into renal tissue. PCR using species-specific primers and sequence analysis revealed that xenotransplanted metanephros, from rat to mouse and similarly from pig to cat, expresses erythropoietin (EPO) of host animal origin.…”
Section: Metanephros Transplantation As a Source Of Organ Regenerationmentioning
confidence: 99%
“…Embryonic kidney rudiments implanted beneath the renal capsule [4,5], within the omentum [5,6] or into tunnels in the cortices of host kidneys [7] become integrated into living animals. Cultured fetal kidneys [8] also become vascularized and form mature glomeruli upon in vivo transplantation.…”
Section: Introductionmentioning
confidence: 99%